Home automatic activation system / Muhammad Raziff Naaim & Muhammad Izwan Azri Azwardi - Naaim, Muhammad Raziff; Azwardi, Muhammad Izwan Azri (2015)
The project is about smart and intelligence clap system for turning off home appliances. This project was proposed to be an automation system by clapping mechanism was used to switch off their electrical appliances, such as light, fan, television, heater etc. The main objectives is to help life more comfortable, especially for the elderly and disabled as they will not have to be actually present near an appliance to turn it on or off. The system focused on using a Digital Signal Processor to process the clap and accordingly control the required appliance. In this project, microphone is used as a sound sensor to detect sound which is clap. Experimental results show that the system has a good response and is cost effective. This system provided solutions for the problems faced by home owners in daily life and make their life easier and more comfortable by proposing a cost effective and reliable solution.